Image_16.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Bhakris are lightweight and easy to pack, and they last several days, making them ideal food for long-distance travel. Koli fishermen pack dozens of bhakris when they venture for deep sea fishing, as they may be unable to cook at sea for days.